Effect of planting density on wood anatomy in Eucalyptus and Acacia from Brazil - Guedes, Taiane Oliveira; Lima, Lidiane Costa; Hein, Paulo Ricardo Gherardi; da Silva, José Reinaldo Moreira; Santos, Leonardo David Tuffi (Instituto de Ecología, A.C., 2018)
The effect of planting density on the anatomical characteristics of wood is still matter of debate. The aim of the study was to investigate the influence of planting density on the variation of wood anatomical elements in Eucalyptus and Acacia trees cultivated in areas of high planting density (monospecific) and low planting density (mixed) stands. The fiber length, fiber width, fiber lumen diameter, cell wall thickness, vessel diameter and vessel frequency were evaluated. The measurements were made from wood discs taken from five Eucalyptus urophylla x E. grandis trees and five Acacia mangium trees grown in high planting density (monospecific plantations, 1667 trees/ha) and in low planting density (mixed stands, 500 trees/ha), totalizing 20 trees at 4.5 years old. Eucalyptus and Acacia produced wood with shorter fibers and smaller vessels in high density stands, when compared to its equivalent in low density. Acacia presented more frequent vessels and fibers with walls thicker than its equivalent in low planting density. Eucalyptus presented longer and thinner fibers and vessels more frequent than Acacia, regardless of planting density. On the other hand, in high planting density, Acacia presented fibers with walls thicker than Eucalyptus and in low density of planting their vessels were larger.